The 62- and 80-kDa subunits of transcription factor IIH mediate the interaction with Epstein-Barr virus nuclear protein 2. - Tong, X (1995)
EBNA 2 (Epstein-Barr virus nuclear antigen 2) is an acidic transactivator essential for EBV transformation of B lymphocytes. We show that EBNA 2 directly interacts with general transcription factor IIH. Glutathione S-transferase (GST)-EBNA 2 acidic domain fusion protein depleted transcription factor IIH activity from a TFIIH nuclear fraction. The p89 (ERCC3), p80 (ERCC2), and p62 subunits of TFIIH were among the proteins retained by GST-EBNA 2. Eluates from the GST-EBNA 2 beads reconstituted activity in a TFIIH-dependent in vitro transcription assay. The p62 and p80 subunits of TFIIH independently bound to GST-EBNA 2, whereas the p34 subunit of TFIIH only bound in the presence of p62. A Trp-->Thr mutation in the EBNA 2 acidic domain abolishes EBNA 2 transactivation in vivo and greatly compromised EBNA 2 association with TFIIH activity and with the p62 and p80 subunits, providing a link between EBNA 2 transactivation and these interactions. Antibodies directed against the p62 subunit of TFIIH coimmunoprecipitated EBNA 2 from EBV-transformed B lymphocytes, indicating that EBNA 2 associates with TFIIH in vivo.